Direct from the Moon [videorecording (DVD)] - Katsumata, Tomoyuki; Kunihara, Yuichi; Aldrin, Buzz (National Geographic, 2009)
Nearly 40 years after Apollo astronauts Neil Armstrong and Buzz Aldrin enthralled the nation when they became the first men to land on the moon, lunar exploration has returned to the headlines as new information is being uncovered about the birth of our solar system. Stunning footage from the Kaguya lunar orbiter has revealed images of the moon and Earth in spectacular detail like never seen before. Explores the past, present and future of lunar expeditions from the Apolla missions to the challenges involved with establishing a lunar outpost and innovations under way that will inspire the next generation of space exploration.